2009
DOI: 10.2106/jbjs.h.00486
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Decreased Bone Mineral Density and Severity of Distal Radial Fractures

Abstract: There is a definite correlation between bone mineral density and the severity of distal radial fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
2
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(88 citation statements)
references
References 8 publications
4
70
2
10
Order By: Relevance
“…In a study of 137 patients with distal radius fractures, Clayton et al [27] found a significant but modest correlation between femoral neck T score measured 3 months after the injury and the probability of malunion defined as dorsal angulation [10°or ulnar variance [3 mm. Our results suggest that T scores may have benefit in identifying patients with high risk of severe malunion if treated with closed reduction and cast.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 137 patients with distal radius fractures, Clayton et al [27] found a significant but modest correlation between femoral neck T score measured 3 months after the injury and the probability of malunion defined as dorsal angulation [10°or ulnar variance [3 mm. Our results suggest that T scores may have benefit in identifying patients with high risk of severe malunion if treated with closed reduction and cast.…”
Section: Discussionmentioning
confidence: 99%
“…Proper classification before the treatment of distal radius fractures is important in the determination of treatment plan. Type C fractures according to AO classification, are difficult to treat surgically due to significant intraarticular extensions and metaphysis defects (Clayton et al, 2009). Multifragmentary nature of fracture shows the severity of trauma and its high energy (Fernandez, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Кроме того, выявлена сильная коррелятивная связь между МПК и степенью тяжести перелома в дистальном отделе лучевой кости [21].…”
Section: обзоры литературы № 3/2013 остеопороз и остеопатииunclassified